Encyclopedia of Global Justice
eReference.
Keywords: This two-volume Encyclopedia of Global Justice, published by Springer, along with Springer's book series, Studies in Global Justice, is a major publication venture toward a comprehensive coverage of this timely topic. The Encyclopedia is an international, interdisciplinary, and collaborative project, spanning all the relevant areas of scholarship related to issues of global justice, and edited and advised by leading scholars from around the world. The wide-ranging entries present the latest ideas on this complex subject by authors who are at the cutting edge of inquiry. The Encyclopedia sets the tone and direction of this increasingly important area of scholarship for years to come. The entries number around 500 and consist of essays of 300 to 5000 words. The inclusion and length of entries are based on their significance to the topic of global justice, regardless of their importance in other areas.